Implementasi Asistensi Mengajar, Adaptasi Teknologi, Dan Administrasi Dalam Program Surabaya Mengajar Sebagai Wadah Berproses Mahasiswa Dengan Terjun Langsung Pada SMPN 39 Surabaya - Kusnul Kotimah (Jurnal Pelayanan Hubungan Masyarakat, 2023)
The Surabaya Teaching program is part of the Freedom to Learn Campus Merdeka (MBKM) policy to enrich student competence by providing opportunities for students to learn outside the classroom by providing assistance to teachers and education staff at the primary and secondary education levels. This program invites students to contribute to improving the quality of learning at the elementary and junior high school levels for one semester. The Surabaya Teaching program is currently the 3rd batch assigned to teach, assist with technology, and assist with school administration and teachers in schools in 3T areas. One of the schools where Surabaya teaches is SMP Negri 39 Surabaya, which is located on Jl. Raya Prapen, Panjang Jiwo, Kec. Tenggilis Mejoyo, Surabaya, East Java. Surabaya Teaching students also have a responsibility in improving the character and interest in learning students who are low. The goals that can be achieved in undergoing the Surabaya Teaching Program batch 3 are a process of adding relationships, adding experience outside the world of lectures, developing students' insights, character and soft skills, encouraging and spurring national development by growing student motivation to participate in development, and increasing the real role and contribution of universities and students in the development of education in Indonesia. The results of this program include improving educational services at these schools in terms of teaching, technology utilization, and administration. It can be concluded that the Surabaya Teaching program provides good benefits for all parties and also provides a lot of experience gained during assignments taking place at SMP Negri 39 Surabaya, starting from the observation, planning, implementation and evaluation activities that take place during activities.